The impact of wasatiyyah/moderation on students’ financial decisions - Wan Husain, Wan Rohaida; Ramlee, Roslily; Syed Mohd Zain, Sharifah Raihan; Jan, Muhammad Tahir (Elsevier, 2021)
Statistics and surveys of literature reveal the disturbing truth of financial prudence among Malaysians, especially the youth. Studies show that today’s youth are easily overwhelmed by the latest trends causing them to spend beyond their means due to impulse-buying behaviour. Individual financial decisions, including spending, savings, borrowing and investment, are generally influenced by one’s materialistic needs as well as one’s level of financial literacy. In consideration of these two main contributing factors, the reported study aims to examine the practice of moderation (wasatiyyah) among Malaysian university students in their financial decision making. A total of 550 questionnaires distributed to students from public universities in central and north Malaysia. Data analysed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). Findings conclude the absence of postulated mediatory influence wasatiyyah exerts on the students’ financial decision. Nevertheless, the adoption of wasatiyyah found to be as influential as students’ financial literacy on their financial decision making. Hence supports the tested hypothesis that wasatiyyah would make students more cautious in financial decision making.